1998
DOI: 10.1023/a:1024762503100
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Differences in response to psychopharmacologic agents according to race has so far primarily focused on investigations related to the response of Asian-American patients to neuroleptics and lithium. In this article, we present evidence which depicts that black patients need lower doses of tricyclic antidepressants (TCAs) than white patients to attain a similar response in the treatment of major depression. Likewise, we also advance that black patients might need lower doses of selective serotonin re-uptake inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Furthermore, this difference did not seem to be related to socio-economic or clinical features. 36 With regard to triciclics antidepressants (TCAs), Africans, Asians, and Hispanics seem to require lower doses than Caucasians, [37][38][39] while this relation was not reported for SSRIs. 39 By contrast, other studies did not found ethnic differences in the clinical response to ADs.…”
Section: Antidepressantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this difference did not seem to be related to socio-economic or clinical features. 36 With regard to triciclics antidepressants (TCAs), Africans, Asians, and Hispanics seem to require lower doses than Caucasians, [37][38][39] while this relation was not reported for SSRIs. 39 By contrast, other studies did not found ethnic differences in the clinical response to ADs.…”
Section: Antidepressantsmentioning
confidence: 99%
“…36 With regard to triciclics antidepressants (TCAs), Africans, Asians, and Hispanics seem to require lower doses than Caucasians, [37][38][39] while this relation was not reported for SSRIs. 39 By contrast, other studies did not found ethnic differences in the clinical response to ADs. An eight-week, open-label clinical trial on patients diagnosed with major depression treated with citalopram, did not report differences in both clinical response and side effects between African-Americans (n = 169) and Caucasians (n = 132), with remission rates of around 50% in both the groups.…”
Section: Antidepressantsmentioning
confidence: 99%
“…Contrary to general beliefs that African/Black populations require higher doses of psychopharmacological agents than the Caucasian population for the treatment of most psychiatric disorders, recent studies have shown that this is not the case. These studies (Varner et al , 1998, 2000; Ruiz et al , 1999) have shown that African/Black populations require smaller doses of tricyclic antidepressants (desipramine, imipramine and nortriptyline) than the Caucasian population for the treatment of major depression and, similarly, smaller doses of selective serotonin reuptake inhibitors (fluoxetine and sertraline).…”
Section: African/black Populationsmentioning
confidence: 99%
“…It has been shown that some diseases such as sickle-cell anemia [ 5 ], cystic fibrosis [ 6 ] and hemochromatosis [ 7 ] are more common in specific ethnic populations due to unique genetic mutations in their genomes; but they are rarely found in others. There are also reports indicating that different populations may have various responses to drugs [ 8 10 ]. These findings demonstrate that haplotypes in human genomics data could be a useful and informative tool in mapping genes that are involves in representative diseases, as well as personalized medicine [ 11 ].…”
Section: Introductionmentioning
confidence: 99%